2016
DOI: 10.1111/gtc.12436
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage inhibits lateral root formation by up‐regulating cytokinin biosynthesis genes in Arabidopsis thaliana

Abstract: Lateral roots (LRs) are an important organ for water and nutrient uptake from soil. Thus, control of LR formation is crucial in the adaptation of plant growth to environmental conditions. However, the underlying mechanism controlling LR formation in response to external factors has remained largely unknown. Here, we found that LR formation was inhibited by DNA damage. Treatment with zeocin, which causes DNA double-strand breaks, up-regulated several DNA repair genes in the LR primordium (LRP) through the signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In the context of DNA-damage induced PCD, ERF115 induction was shown to depend partially on SOG1 activity (Johnson et al, 2018). DDR was also shown to impact lateral root formation by modulating cytokinin signaling (Davis et al, 2016), and to account for the reduction of hypocotyl growth triggered by UV (Biever et al, 2014), suggesting that its activation could contribute to the well-known plasticity of plant development according to external conditions.…”
Section: Role Of the Plant Ddr In Abiotic Stress Responsesmentioning
confidence: 99%
“…In the context of DNA-damage induced PCD, ERF115 induction was shown to depend partially on SOG1 activity (Johnson et al, 2018). DDR was also shown to impact lateral root formation by modulating cytokinin signaling (Davis et al, 2016), and to account for the reduction of hypocotyl growth triggered by UV (Biever et al, 2014), suggesting that its activation could contribute to the well-known plasticity of plant development according to external conditions.…”
Section: Role Of the Plant Ddr In Abiotic Stress Responsesmentioning
confidence: 99%
“…We showed that polyamines alleviated the inhibitory effect caused by MMC on the primary-root growth. Although Davis et al (2016) already showed that several types of genotoxic agents (including MMC) inhibit the growth of primary roots and reduce lateral root density, 23 our study is the first to provide evidence that polyamines contribute to tolerance against plant growth inhibitions caused by a DNA-damaging chemical. In this study, we have no data to prove that the MMC treatments used in our experiments are enough to induce DNA cross-linking in the plant genome.…”
Section: Putrescinementioning
confidence: 67%
“…21,22 It has been previously reported that transcript levels of AtBRCA1 and AtRAD51 are markedly increased in A. thaliana by treating it with zeocin, a double strand break (DSB)-inducing agent. 23,24 When we examined the MMC-dependent transcriptional changes of the AtBRCA1 and AtRAD51 genes with quantitative real-time PCR, AtBRCA1 and AtRAD51 gene expressions increased by approximately 8.8-fold and 7.2-fold, respectively, by 24 h after transferring seedlings to the MMC[+] medium (Figure 3(a,b)). Next, we assessed the polyamine-dependent transcriptional changes of seedlings grown in the medium without MMC (termed MMC[-]) medium.…”
Section: Putrescinementioning
confidence: 99%
“…In the present study, we have not investigated the involvement of GH3.17 and PIN5 in the DDR, but it is possible that enhanced cytokinin biosynthesis affects the auxin level in the LRC and reduces the meristem size. We previously demonstrated that DNA damage upregulates cytokinin signalling in the lateral root (LR) primordium and inhibits LR formation 51 . However, it has remained unknown whether the cytokinin level increases in the LR primordium and how LR development ceases after DNA damage.…”
Section: Discussionmentioning
confidence: 99%